Stunting Policy as Civic Education: Reframing Public Policy as a Civic-Embedded Process in Indonesia - Rahmadani Yusran; Asrinaldi Asrinaldi; Azwar Azwar; Tengku Rika Valentina (Journal of Moral and Civic Education, 2026)
Indonesia’s stunting reduction policies are predominantly framed as technical interventions. This article offers an alternative perspective, positioning these policies as an arena for community-level citizenship education. Employing a qualitative interpretive policy analysis of national documents and scholarly reports, the study utilizes deductive-inductive coding across three dimensions: civic literacy, social solidarity, and participatory negotiation. The findings reveal that implementation generates both technical outputs and critical civic learning processes, where citizens negotiate rights and engage in local decision-making. These insights culminate in the SPACE Model (Stunting Policy as Civic Education), which conceptualizes stunting reduction as a civic-embedded process. This model integrates dual goals of health and empowerment, emphasizing meaningful participation, frontline mediation, and learning-accountability loops. The article concludes that policy success must be evaluated beyond clinical prevalence, accounting for its contribution to strengthening civic capacity and democratic engagement at the community level. Further research suggest that stunting policy reduction needs to look at religious and cultural approaches.